Pemulihan Trauma: Strategi Pemulihan Trauma Korban Pelecehan Seksual - Muhammad Putra Dinata Saragi; Khusnul Khotimah; Mawaddah Mawaddah; Dika Sahputra; Annisa Arrumaisyah Daulay (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
Sexual harassment situations, which are common not just in metropolitan regions but also in rural ones, can no longer be viewed as ordinary incidents. This is one of the reasons why victims may experience trauma that may affect their well-being, recovery from the trauma is required. Which has as its goal to examine the trauma recovery method for sexual harassment victims within the organization. In order to broadly characterize the research's findings, descriptive qualitative research methodologies were used in this study, along with data gathering strategies such literature reviews, interviews, and employing triangulation techniques to check the accuracy of the data. It was discovered that the Binjai City Women and Children Protection Service employs monitoring, evaluation, social reintegration, rehabilitation, mentorship as a tactic for the trauma recovery of sexual assault victims.